Role of Educational Broadcasting in Shaping Public Opinion in Nigeria - Jesulayomi Charis Olu-Oladele; Mmesomachukwu Chukwuemeka Iloh; Chidinma N. Ejekwu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
This paper tries to look into the role of educational broadcasting in the shaping of public opinion about various pertinent problems, such as environmental sustainability, health education, and civic involvement. The paper argues that through aid to educational broadcasting, public opinion is shaped in ways that provide for disseminating information that is accurate, media literacy, and critical thinking, encouraging discourse and community engagement. The literature review in this context comes with an extensive review with empirical studies. In essence, the paper reviews the probable drawbacks and challenges of educational broadcasting with fears of bias and false information. The research that follows attempts to untangle this complicated interrelationship of public opinion and educational broadcasting to provide further insight into the impacts of the medium on cultural attitudes and behaviors for policymakers, educators, and media professionals. Finally, the present study has the purpose of providing insight into the efficient application of educational television as a vehicle able to provoke social change in an ever-complex media environment.